Regions' Economic Autonomy in the New Reality - Bochko, Vladimir Stepanovich (Economy of Regions, 2016)
The paper discloses the understanding of new reality (normality) for Russia that consists in the strengthening of the role of a man-personality and in the expansion of the economic autonomy of the territories in their interaction with the federal center. The rationale is based on a hypothesis according to which in the conditions of new reality, the increase of the well-being of the population and the overcoming of economic inequality between the territories are provided by the expansion of their economic independence as it leads to the increase of their intellectual, engineering and manufacturing potential. In the research, the author used the basic concepts of the classical economic theory, the theory of behavioural economics, interdisciplinary approach and statistical grouping method. The dynamics of the economic independence of the territories, which is manifested in the decrease in a number of donor regions and the socio-economic dividing of the territories, is shown. The assumption is proved that the consequences of the territorial stratification are the restraining of the growth of their socio-economic development and possibility probable emergence of «regional peripheral economy» with the property of the dependence of the periphery on the center, the decrease in a local initiative, the inhibition of technological development. The need to use the social psychology of the population, the psychological sets of economic development, «the second invisible hand of the market» and soft power to overcome the «regional peripheral economy» is revealed. The result of the research is the proof that the expansion of the economic independence of the territories is not only the increase of the self-isolation of regions and municipalities, but also the need to save the considerable part of the income from the production of goods and services created by the local population under control of the regional and municipal authorities and direct it to the increase of the well-being of the population of the territory. The idea of creating the legal document to provide and strengthen the economic independence of territories is offered; the suggestions on the principles of its contents and structuring are stated.